Evil and Creation : Historical and Constructive Essays in Christian Dogmatics. - Luy, David (Studies in historical & systematic theology., 2020)
In Evil and creation essayists investigating how the doctrine of creation relates to moral and physical evil pursue philosophical and theological analyses of evil rather than neatly solving the problem of evil itself.